2007 IEEE/ACS International Conference on Computer Systems and Applications 2007
DOI: 10.1109/aiccsa.2007.370881
|View full text |Cite
|
Sign up to set email alerts
|

Session awareness issues for next generation cluster based network load balancing frameworks

Abstract: While a lot of researches focused on how to efficiently spread the offered network load on the available cluster resources, less interest has been granted to the impact of the used mechanisms on the reliable execution of the upper layer services. On the other hand, emerging NGN services as well as some of the already familiar services involve multiple flows during the lifespan of a single endto-end session, hence, raising the challenge of session awareness while processing the incoming network traffic.In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Datagrams which are subject to content inspection are those being exchanged over the signalling flows. Indeed, in [3] we showed that multiple-flow based sessions such as video streaming sessions negotiate data flow identifiers and control data flow identifiers using messages exchanged over the main signalling flow. A searched pattern is a particular application level protocol header field holding the information necessary to identify the possible next incoming flows associated to an already established session.…”
Section: A the Session Identifier Enginementioning
confidence: 99%
See 3 more Smart Citations
“…Datagrams which are subject to content inspection are those being exchanged over the signalling flows. Indeed, in [3] we showed that multiple-flow based sessions such as video streaming sessions negotiate data flow identifiers and control data flow identifiers using messages exchanged over the main signalling flow. A searched pattern is a particular application level protocol header field holding the information necessary to identify the possible next incoming flows associated to an already established session.…”
Section: A the Session Identifier Enginementioning
confidence: 99%
“…The cluster global load is considered as critical when it goes beyond the third threshold 3 T . Rather than interrupting the already established sessions leading them to be restarted from scratch, we suggest to instantaneously degrade their QoS.…”
Section: B the Session Aware Admission Control Engine (Sa2c)mentioning
confidence: 99%
See 2 more Smart Citations